The performance of IoT based health monitoring system in various environments / C.S. Gaston Ravin Dias - C.S. Gaston, Ravin Dias (2019)
Nowadays, "Internet of Things‟ (IoT) is playing an important role in all industries and soon it will become a dominant application which will influence our day-to-day life. IoT means the interconnections of all the devices what we use in our day-to-day life via the internet which will provide the facilities of operating, controlling, data collection and analyzing of those devices from anywhere around the world. In these modern days, due to the booming growth in Healthcare Industry, many researches are carried out on these IoT concept and several techniques have been widely applied in order to provide best medical assistance with cutting edge technology to provide less effort and low cost healthcare services. „Telemedicine‟ and „Remote Patient Monitoring‟ are some other techniques used in the healthcare industry which comes under the applications of IoT in Healthcare. Basically, all these concepts help to monitor the patients without being with them physically or in other words „Remote Monitoring‟, which gives enough space for both patient and healthcare providers and many more advantages physically and economically. In this project, performances of IoT based Healthcare Monitoring System in various environments are studied. The related techniques in the literature are reviewed in order to understand the existing techniques and the functions of such systems. A prototype of a standard Remote Patient Monitoring system has been developed and tested in various environments. Results have indicated that the applied Network Type and its Signal Strength have impacts on reducing the effectiveness of such Systems. Ways to improve the system performance are discussed in this research report.